(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
This article explores some aspects of the pandemic emergency and aims to analyse the legal basis of the lockdown. It focuses on the definition of the “state of exception”, in order to evaluate its function as a key concept in public law discourse.